2021
DOI: 10.1080/17425247.2021.1981286
|View full text |Cite
|
Sign up to set email alerts
|

Safety of recombinant human hyaluronidase PH20 for subcutaneous drug delivery

Abstract: Introduction:The glycosaminoglycan hyaluronan forms a gel-like substance, which presents a barrier to bulk fluid flow in the subcutaneous (SC) space, limiting SC drug delivery volume and administration rates. Recombinant human hyaluronidase PH20 (rHuPH20) acts locally to temporarily remove this barrier, facilitating rapid SC delivery of large volumes and/or high doses of sequentially or coadministered therapeutics. Areas covered: An extensive clinical and post-marketing dataset of safety and immunogenicity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 68 publications
1
9
0
Order By: Relevance
“…A total of 8 patients developed non‐neutralizing binding anti‐rHuPH20 antibodies (≥1:160), which were not associated with an increased incidence of AEs, or local or systemic reactions. The lack of clinical relevance of binding anti‐rHuPH20 antibodies in ADVANCE‐CIDP 1 is consistent with an analysis of a study of fSCIG 10% for primary immunodeficiency diseases, as well as an extensive review of hyaluronidase‐conjugated antibody therapeutics in a multitude of diseases 37,38 …”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…A total of 8 patients developed non‐neutralizing binding anti‐rHuPH20 antibodies (≥1:160), which were not associated with an increased incidence of AEs, or local or systemic reactions. The lack of clinical relevance of binding anti‐rHuPH20 antibodies in ADVANCE‐CIDP 1 is consistent with an analysis of a study of fSCIG 10% for primary immunodeficiency diseases, as well as an extensive review of hyaluronidase‐conjugated antibody therapeutics in a multitude of diseases 37,38 …”
Section: Discussionsupporting
confidence: 68%
“…The lack of clinical relevance of binding anti-rHuPH20 antibodies in ADVANCE-CIDP 1 is consistent with an analysis of a study of fSCIG 10% for primary immunodeficiency diseases, as well as an extensive review of hyaluronidase-conjugated antibody therapeutics in a multitude of diseases. 37,38 This study was affected by the COVID-19 pandemic and was closed to recruitment before the target sample size was achieved. This might have limited the characterization of the safety profile.…”
Section: Discussionmentioning
confidence: 99%
“…Hyaluronidases (Hyals) are a large class of glycosidases that predominately catalyze the degradation of hyaluronic acid (HA) (Fronza et al, 2016;Khan et al, 2018). Due to their functions of anesthetic assistance, reducing intraocular pressure, facilitating drug absorption, and resistance to tumor signaling, Hyals have been widely used in medical fields (Locke et al, 2019;Feng et al, 2021;and Knowles et al, 2021). Based on the differences in their catalytic mechanisms and end products, Hyals are classified into three families (Bookbinder et al, 2006;El-Safory et al, 2010;and Kang et al, 2018): hyaluronate 4-glycanohydrolases (EC 3.2.1.35, mammalian hyaluronidases, hydrolyzing the β-1,4 glycosidic bonds of HA, and furnishing tetrasaccharide as the main product), hyaluronate 3-glycanohydrolases (EC 3.2.1.36, leech hyaluronidases, hydrolyzing the β-1,3 glycosidic bonds of HA, and generating tetra-and hexasaccharide end products), hyaluronate lyases (EC 4.2.2.1, bacterial lyases, degrading HA by a β-elimination reaction, and yielding unsaturated disaccharides as the main products).…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][27][28][29][30] Although physiological relevance is unclear given the minimal volume of hyaluronidase within these formulations (rHuPh20 content ranges from 2400 to 30,000 units in currently approved subcutaneous mAb formulations). 31 If subcutaneous administration serves as a portal of entry for skin commensals which typically are gram-positive bacteria that are capable of producing biofilms, the risk of distal spread of infection after exposure to exogenous hyaluronidase may have been minimised in studies such as the PrefMab study which demonstrated higher use of broad spectrum antibiotic prophylaxis in the subcutaneous arm compared to the intravenous arm (14% vs 9%), a strategy that is not widely supported due to the risk of emergence of antibiotic resistance and ensuing complications. This was the only RCT in this meta-analysis that tended towards lower rate of serious infections in the subcutaneous arm.…”
Section: Discussionmentioning
confidence: 99%